Pengaruh Kualitas Layanan Mobile JKN terhadap Kepuasan Pengguna di Pusat Layanan Kesehatan Universitas Negeri Semarang - Wahyuti Risma Dhani; Fitri Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
The JKN mobile application in Semarang City in 2021 has been used by 228,965 people, while it is not comparable to BPJS Health participants, which amounted to 2,664,532 people and if it is percented, only 11% of JKN mobile users. The purpose of this study was to determine the effect of JKN mobile service quality on user satisfaction. This research was conducted using a quantitative cross-sectional design. The sample size was calculated using the Lameshow formula and the results obtained were 385 respondents with the inclusion criteria of JKN mobile users at the Semarang State University Service Center. This research was conducted from September to December 2024. The results showed that the core scale of service quality that has an influence on user satisfaction is efficiency (p value 0.000) and reliability (p value 0.005). The core scale of service quality that has no influence on satisfaction is fulfillment (p value 0.068) and confidentiality (p value 0.404).